Empowerment of Rural Communities from the Perspective of the Quran: Towards Social Entrepreneurship through Village-Owned Enterprises - Tirmidzi, Ayi Yusri Ahmad; Riyadi, Dedi Slamet (Mashadiruna Jurnal Ilmu Al-Qurân dan Tafsir, 2023)
Poverty in Indonesia is often a concentrated issue in rural areas. Although the government has provided various incentives to improve the rural economy, the results have not brought significant change. This is due to the incomplete effectiveness of rural community empowerment management, resulting in a lack of creativity and innovation in villages. This article aims to explore the concept of community empowerment from the perspective of the Quran, using a social entrepreneurship model through Village-Owned Enterprises (BUMDes) as a solution to address rural poverty. The social entrepreneurship model is chosen because of its integration of social and economic issues and its invitation for the entire village community to participate in this change. Using a descriptive-analytic approach based on the thematic interpretation of the Quran, this article concludes that the Quran provides guidelines for community empowerment that include at least three crucial aspects: 1) opportunity, 2) capacity, and 3) authority. These three aspects form the basis for the implementation of social entrepreneurship through BUMDes in a way that has the potential and proportionality to empower rural communities. One example of a village that has successfully implemented this model is Kertayasa Village. To date, Kertayasa Village has achieved relative success in building social entrepreneurship through BUMDes. The success of this social entrepreneurship model reflects an approach that prioritizes social welfare collectively over individual economic gains.